Physical activity of the society - Samek, Ilona; Jańczyk, Magdalena; Milanowska, Joanna (Journal of Education, Health and Sport, 2021)
Introduction: Physical activity is defined as human body movement performed by skeletal muscles. It is part of a healthy lifestyle and is linked to goals such as health and happiness. It shows beneficial effects on the human body as well as on the human mental state. Aim: To present the public’s opinion on physical activity. Material and methods: The study was conducted by using the author’s questionnaire. 198 questionnaires were obtained and then analyzed. Results: Women (76.8%) and men (23.2%) participated in the study. The average height of women was 169.5 cm, while that of men was 178.3 cm. The average weight of women was 65.7 kg and men 79.2 kg. The analysis shows that 61.1% of the respondents engage in regular physical activity every day. Seasonal activity is different, with only 29.3% of respondents engaging in it. The most popular sport was cycling, chosen by almost 1/3 of the respondents. Also popular was the gym (29.8%). In winter the respondents most often went skiing (19.7%) and skating (19.2%), while in summer they went roller-skating (18.6%). Men more often opted for activities that contribute to good physical condition, while women preferred body shaping exercises. The analysis also showed that for 34.0% of the respondents health is the most important goal. They also focused on staying fit (24.2%) and silhouette (23.2%). Almost all respondents described their motivation as high (88.9%) and believe that they will achieve their physical activity goal (81.8%). Conclusions: The majority of the population knows the importance of physical activity on a daily basis and is motivated to do so. The type of activity varies according to gender, season and individual preference. However, most people say that the main purpose of being active is to stay healthy.